Mitigating Students’ Anxiety: The Role of Resilience and Mindfulness Among Chinese EFL Learners - Shen, Yanfei (Frontiers in Psychology, 2022)
To manage the undesirable effect of anxiety on students, a wide scope of research has been dedicated to determining the triggers of anxiety and pedagogical interferences that can assist students with mitigating anxiety. Mindfulness is a relaxation strategy that has been related to constructive impacts when utilized as a managing technique for stress and anxiety. Originating from the construct of mindfulness, there is a multidimensional conception acknowledged as resilience as one of the notions in the Positive Psychology (PP) literature, which highlights the organizations and individuals’ strengths and self-control to comply with accidental states. Given the eminence of mindfulness and resilience in learning situations, the present study sets forth to examine the role of these constructs in alleviating English as a foreign language (EFL) learners’ anxiety. To meet this objective, 502 Chinese EFL learners took part in this research. They were asked to respond to the three questionnaires, namely resilience, mindfulness, and anxiety. To answer the research question of the study, a linear multiple regression was run and the findings demonstrated that mindfulness and resilience together could significantly predict anxiety. Consistent with the findings, some recommendations are presented concerning the implications of the present research.